Sphingosine and dihydrosphingosine as biomarkers for multiple sclerosis identified by metabolomic profiling using coupled UPLC-MS. Issue 41 (5th October 2017) - Ward, Sean; Page, Michael I.; McHugh, Patrick; Powles, Nicholas T.
Abstract : The project aim was to identify differences in the metabolomic profiles in the serum of patients with multiple sclerosis (MS), those with neuropathic pain (NP) and those with both MS and NP compared with controls and to identify potential biomarkers of each disease state. Abstract : The project aim was to identify differences in the metabolomic profiles in the serum of patients with multiple sclerosis (MS), those with neuropathic pain (NP) and those with both MS and NP compared with controls and to identify potential biomarkers of each disease state. Metabolomic profiling was performed using ultra-high-performance liquid chromatography coupled to mass spectrometry and the data analysis involved parametric methods, principal component analysis, and discriminating filter analysis to determine the differences between disease and control serum samples. Sphingosine and dihydrosphingosine were identified as significant biomarkers.